Complement C3 gene: Expression characterization and innate immune response in razor clam Sinonovacula constricta. (August 2016) - Peng, Maoxiao; Niu, Donghong; Wang, Fei; Chen, Zhiyi; Li, Jiale
Abstract: Complement component 3 (C3) is central to the complement system, playing an important role in immune defense, immune regulation and immune pathology. Several C3 genes have been characterized in invertebrates but very few in shellfish. The C3 gene was identified from the razor clam Sinonovacula constricta, referred to here as Sc-C3 . It was found to be highly homologous with the C3 gene of Ruditapes decussatus . All eight model motifs of the C3 gene were found to be included in the thiolester bond and the C345C region. Sc-C3 was widely expressed in all healthy tissues with expression being highest in hemolymph. A significant difference in expression was revealed at the umbo larvae development stage. The expression of Sc-C3 was highly regulated in the hemolymph and liver, with a distinct response pattern being noted after a challenge with Micrococcus lysodeikticus and Vibrio parahemolyticus . It is therefore suggested that a complicated and unique response pathway may be present in S. constricta . Further, serum of S. constricta containing Sc-C3 was extracted. This was activated by LPS or bacterium for verification for function. The more obvious immune function of Sc-C3 was described as an effective membrane rupture in hemocyte cells of rabbit, V. parahemolyticus and Vibrio anguillarum. Thus, Sc-C3 plays an essential role in the immune defense of S. constricta . Highlights: Isolate and characterize complement C3 ( Sc - C3 ) gene from the razor clam, Sinonovacula constricta . Sc-C3 transcripts can express widely in tested tissues and Sc - C3 may be play an importance role in innate immune for larva and adult. Sc-C3 transcripts expression can be induced significantly by bacterial challenge. Sc-C3 protein can be performed effectively function for bacteriolytic and hemolytic.